(3fhQ GdaJGhis - (3eUWaj Hf CMeO GdcQfjTj,J (B1093 (3g` s
(3ChdgG (B:s
(3cJGH GdWgGQI hjfHZi Cf jchf Hjf HFQ GdHGdhYI hHjf HFQ GdeGA ebOGQ eGdG JUd GdfLGSI Edi HFQ GdeGA s
(3BNQgG (B:s
(3hai GdSjQ GdcHjQ jVef dCfg bHV dfaSg aTGHg GdZVH , fSN ef GdUMjM eG PcQ ai GdSjQ ef GdMGhi ddRGgOi ai HGH CMcGe GdHjhY GdaGSOI hGdMeO ddg ChdkG hBNQkG , hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH GdeNWhW HMHQ CShO hCMeQ hCRQb s
(3hddMHQ hGdCShO fTY TF Ydi HYV GdUaMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B441s
Keywords: (3CUhd Gdabgs